Digital promotion of Kazakhstan business universities for generation Z applicants - Zarubina, V.R.; Zarubin, M.Yu.; Esenkulova, Zh.Zh. (BUKETOV BUSINESS REVIEW, 2024)
Object: to determine the assessment of the effectiveness of digital channels for promoting educational services of business universities for representatives of Generation Z. Methods: When writing the article, the methods of analysis, synthesis, description, expert assessment, generaliza tion using analytical web tools similarweb.com, pagespeed.web.dev, wordstat.yandex.ru were used. The analysis of the websites of leading business universities of Kazakhstan was carried out by performance parameters, search engine op timization, recommendations, special features, number of visits, targeting by regions and countries, audience de mographics, marketing channels. An assessment of the popularity of queries by the name of universities in the Eurasian space was made. An assessment of the search queries of visitors to the websites of business universities was carried out. Findings: based on the conducted research, key and additional channels for promoting educational services of Ka zakhstani business universities, in demand by zoomers, were proposed. In a competitive environment, the concentration of efforts to promote educational services of business universities is focused on significant and effective marketing channels. A review of marketing channels leading to university websites allows us to draw conclusions about the un derutilization of social networks. Conclusions: focusing on the proposed digital channels will allow business universities to focus their efforts on popular marketing channels, ensure an increase in the conversion rate, and transform the potential target market from regional to international.